Inhibition of PI3Kδ Differentially Regulates Poly I:C– and Human Metapneumovirus–Induced PD–L1 and PD–L2 Expression in Human Bronchial Epithelial Cells - Ogawa, Tomohiro; Kan-o, Keiko; Shiota, Ayaka; Fujita, Akitaka; Ishii, Yumiko; Fukuyama, Satoru; Matsumoto, Koichiro (Frontiers in Immunology, 2021)
Bronchial epithelial cells are front sentinels eliciting innate and adaptive immunity to respiratory viral pathogens. Recognition of viral double-stranded RNA induces antiviral interferon (IFN) responses in bronchial epithelial cells. Co-inhibitory molecules programmed cell death 1 ligand 1 (PD-L1) and ligand 2 (PD-L2) were also induced on bronchial epithelial cells, which bind programmed cell death 1 on T cell and inhibit the function of virus-specific cytotoxic T lymphocyte. A previous study showed that antiviral type I IFN increased PD-L1 and PD-L2 expression in cultured melanoma cells. However, it remains unknown whether antiviral IFNs affect PD-L1 and PD-L2 expression in bronchial epithelial cells. In addition, we previously reported that inhibition of PI3Kδ signaling enhanced antiviral IFN responses in human primary bronchial epithelial cells (PBECs). Here we assessed the effect of exogenous IFNs or a selective PI3Kδ inhibitor IC87114 on PD-L1 and PD-L2 in PBECs stimulated with a synthetic double-stranded RNA poly I:C or human metapneumovirus. Treatment with IFNβ or IFNλ increased PD-L1 and PD-L2, and IFNβ or IFNλ treatment plus poly I:C further increased both expressions. Treatment with IC87114 or transfection with siRNA targeting PI3K p110δ enhanced poly I:C–induced gene and protein expression of PD-L2, whereas IC87114 suppressed poly I:C–induced PD-L1. IC87114 enhanced poly I:C–induced gene expression of IFNβ, IFNλ, and IFN-regulated genes via increased TBK1 and IRF3 phosphorylation. Transfection with siIRF3 counteracted the enhancement of poly I:C–induced PD-L2 by IC87114, whereas IC87114 suppressed poly I:C–induced PD-L1 regardless of transfection with siNC or siIRF3. Similar effects of IC87114 on PD-L1 and PD-L2 expression were observed in human metapneumovirus–infected PBECs. We showed for the first time that type I and type III IFNs induced the expression of PD-L1 and PD-L2 in PBECs. Our findings suggest that during viral infections, inhibition of PI3Kδ differentially regulates PD-L1 and PD-L2 expression in bronchial epithelial cells.